Elastic Moduli and Electron-Phonon Coupling Constant of NdBa2Cu3-xFexO7-δ Superconductor - Abd-Shukor, R.; Chew, C. M.; Tang, M. S.; Nor-Azah, N. J.; Chiu, W. S.; Chen, S. K.; Nasir, M. N.Mohd; Uskenbaev, Daniyar (Penerbit Universiti Kebangsaan Malaysia, 2026)
The ultrasonic method is very sensitive in determining the role of phonons in the mechanism of superconductivity. In this research, the longitudinal velocity, vL and shear velocity, vs for NdBa2Cu3-xFexO7-δ superconductors with x = 0, 0.02 and 0.05 have been measured between 80 K and around 220 K at a frequency of 10 MHz. NdBa₂Cu₃O₇ exhibited an onset transition temperature, Tc-onset of 93 K and the x = 0.02 sample showed Tc-onset of 58 K while the x = 0.05 showed no transition temperature. The longitudinal and shear velocities increased monotonically with decreasing temperature down to 80 K. The Debye temperature, θD, decreased with Fe doping. For NdBa2Cu3, θD is 370 K, while for the Fe-doped samples it is reduced to 314 K (x = 0.02) and 265 K (x = 0.05), respectively. This decrease showed lattice softening when the superconducting property was suppressed. The electron-phonon coupling constant of NdBa2Cu3 according to the weak coupling limit of the BCS theory is λBCS = 0.67, while in the two-dimensional van Hove scenario, λvH2 = 0.023. For the x = 0.02 sample, λBCS = 0.55 and λvH2 = 0.020. These λvH2 values are consistent with the measured values reported in superconducting cuprates reported by other researchers. This work showed that the electron-phonon coupling together with the infinite density of states at the Fermi level as suggested in the two-dimensional van Hove scenario can be used to explain high temperature superconductivity in the NdBa2Cu3 superconductor.